Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium. Issue 2 (3rd April 2021) - Fix, Jonathan; Annesi-Maesano, Isabella; Baldi, Isabelle; Boulanger, Mathilde; Cheng, Soo; Cortes, Sandra; Dalphin, Jean- Charles; Dalvie, Mohamed Aqiel; Degano, Bruno; Douwes, Jeroen; Eduard, Wijnand; Elholm, Grethe; et al.
ABSTRACT: Purpose : Respiratory hazards of farming have been identified for centuries, with little focus on gender differences. We used data from the AGRICOH consortium, a collective of prospective cohorts of agricultural workers, to assess respiratory disease prevalence among adults in 18 cohorts representing over 200, 000 farmers, farm workers, and their spouses from six continents. Methods : Cohorts collected data between 1992 and 2016 and ranged in size from 200 to >128, 000 individuals; 44% of participants were female. Farming practices varied from subsistence farming to large-scale industrial agriculture. All cohorts provided respiratory outcome information for their cohort based on their study definitions. The majority of outcomes were based on self-report using standard respiratory questionnaires; the greatest variability in assessment methods was associated with chronic obstructive pulmonary disease (COPD). Results : For all three respiratory symptoms (cough, phlegm, and wheeze), the median prevalence in men was higher than in women, with the greatest difference for phlegm (17% vs. 10%). For asthma, women had a higher prevalence (7.8% vs 6.5%), with the difference associated with allergic asthma. The relative proportion of allergic asthma varied among cohorts. In two of eight cohorts for women and two of seven cohorts for men, allergic asthma was more common than non-allergic asthma. Conclusions : These findings indicate that respiratory outcomes are common among farmers around the world despite differences in agricultural production. As women in the general population are at higher risk of asthma, exploring gender differences in occupational studies is critical for a deeper understanding of respiratory disease among agricultural workers.